2D Ti3C2Tx MXenes: Visible Black but Infrared White Materials. Issue 41 (31st August 2021) - Li, Yang; Xiong, Cheng; Huang, He; Peng, Xudong; Mei, Deqing; Li, Meng; Liu, Gongze; Wu, Maochun; Zhao, Tianshou; Huang, Baoling
Abstract: Black inorganic materials with low infrared absorption/emission (or IR white) are rare in nature but highly desired in numerous areas, such as solar–thermal energy harvesting, multispectral camouflage, thermal insulation, and anti‐counterfeiting. Due to the lack of spectral selectivity in intrinsic materials, such counter‐intuitive properties are generally realized by constructing complicated subwavelength metamaterials with costly nanofabrication techniques. Here, the intrinsically low mid‐IR emissivity (down to 10%) of the 2D Ti3 C2 Tx MXene is reported. Associated with a high solar absorptance (up to 90%), it embraces the best spectral selectivity among the reported intrinsic black solar‐absorbing materials. Its appealing potential in several of the aforementioned areas is experimentally demonstrated. First‐principles calculations reveal that the IR emissivity of MXene relies on both the nanoflake orientations and terminal groups, indicating great tunability. The calculations also suggest more potential low‐emissivity MXenes including Ti2 CTx, Nb2 CTx, and V2 CTx . This work opens the avenue to further exploration of a family of intrinsically low‐emissivity materials with over 70 members. Abstract : The ultralow infrared emissivity of the 2D Ti3 C2 Tx MXene is experimentally demonstrated. First‐principles calculations confirm this discovery and reveal other MXenes such as Ti2 CTx, Nb2 CTx, and V2 CTx are also low‐emissivity materials. Such intrinsically visible black but infrared white materials that are rare in nature show great potential in solar–thermal conversion, multispectral camouflage, thermal insulation, and anti‐counterfeiting applications.